PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PELAJARAN BIOLOGI MATERI METABOLISME SEL DENGAN MENGGUNAKAN PERCOBAAN SACH DAN PERCOBAAN INGENHOUZS DI KELAS XII IA1 SMA NEGERI 2 MAUMERE - FLORENTINA JUN DE ROSARI (JURNAL EKONOMI, SOSIAL & HUMANIORA, 2020)
This study aims to determine whether learning through experimental methods can improve biology learning outcomes of students of class XII IA1 at SMA Negeri 2 Maumere on cell metabolic material. The method used is classroom action research (CAR) which consists of two cycles. The subject of the research was class XII IA1 of SMA Negeri 2 Maumere in the Academic Year 2019/2020 of 30 students. Data analysis uses descriptive comparative methods, namely by comparing student test scores, the results of observations of teachers and the results of interviews from the initial conditions with the results achieved from each cycle and analysts in cycle I and cycle II with the application of the experimental method. At the end of the second cycle it was known that an increase had occurred from the first cycle of 75 and over as many as 20 students, the value of 75 to 10 students who completed only 82.35%, while those who did not complete 17.64%. In the second cycle, the value of 75 and above was 28 students and 75 and below were 2 students, so the completion rate increased to 94.11%, while those who did not complete 5.88%. Thus the majority of students in class XII IA1 of SMA Negeri 2 Maumere experienced an increase in learning outcomes through experimental methods on cell metabolism, especially the sub concept of photosynthesis.